IMPLEMENTASI KEBIJAKAN PROGRAM ADIWIYATA DALAM UPAYA MEWUJUDKAN PENDIDIKAN LINGKUNGAN HIDUP DI SEKOLAH DASAR - Rina Rina; Rika Anggela (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2024)
Abstract. Adiwiyata is the highest award in the environmental sector for schools that are deemed to have been able to actualize environmental culture in all aspects of school activities. For this reason, researchers want to know objectively and systematically regarding the implementation of the Adiwiyata policy in realizing Environmental Education at SD N 34 Pontianak City. Specifically, researchers want to know the planning, implementation and evaluation of environmental education as an Adiwiyata program in schools. The research method used is a qualitative method in the form of descriptive research. The type of data used in this research is data obtained directly from the main source of information by the researcher coming directly to the research location, namely SDN 34 Pontianak City. Data sources are school principals, teachers and students. The analysis technique in this research is interactive with data validation in the form of Source and Technique Triangulation. The research results illustrate that the implementation of the Adiwiyata Policy in an effort to realize Environmental Education in Elementary Schools can be seen through the Planning, Implementation and Evaluation of Environmental Education activities at SD N 34 Pontianak City. To be able to realize Environmental Education requires cooperation from various parties, including the community, school residents and stakeholders.